(untitled) (LEARNing Landscapes, 2019)
In this article, we present a set of poems that have helped us to come to know teaching in particular ways. We argue that the artistic medium of poetry can provide unique and important insights into what it is like to live through classroom moments. Using connoisseurship as our mode of inquiry, we share these poems, our interpretations of these poems, and our justification for why poetry is a valid way of knowing teaching. We invite our readers to join us in exploring the aesthetic dimension of teaching.